Effects of a simulation‐based education programme on delirium care for critical care nurses: A randomized controlled trial. (22nd June 2021) - Ho, Mu‐Hsing; Yu, Lee‐Fen; Lin, Pu‐Hung; Chang, Hui‐Chen (Rita); Traynor, Victoria; Huang, Wen‐Cheng; Montayre, Jed; Chen, Kee‐Hsin
Abstract: Aims: To evaluate the effects of a simulation‐based education programme on critical care nurses' knowledge, confidence, competence and clinical performance in providing delirium care. Design: Single‐blinded randomized controlled trial. Methods: Registered nurses who work in intensive care units were recruited from a university‐affiliated acute major metropolitan teaching hospital. The intervention group received: (i) five online‐learning delirium care videos, (ii) one face‐to‐face delirium care education session and (iii) a simulation‐based education programme with a role‐play scenario‐based initiative and an objective structured clinical examination. The control group received only online videos which were the same as those provided to the intervention group. Delirium care knowledge, confidence, competence, and clinical performance as outcomes were collected at: baseline, immediately after intervention, and within 6 weeks post‐intervention to test whether there were any changes and if they were sustained over time. Data were collected between 2 October and 29 December 2020. The repeated‐measures analysis of variance was used to examine for changes in delirium care knowledge, confidence, and competence within groups. Results: Seventy‐two critical care nurses participated with 36 each allocated to the intervention group and control group. No statistically significant difference was observed between the two groups in outcome variables at 6 weeks post‐intervention. In the intervention group, significant within‐group changes were observed in terms of delirium care knowledge, confidence, and competence over time. By contrast, no significant changes were observed in outcome measures over time in the control group. Conclusion: The simulation‐based education programme is an effective and feasible strategy to improve delirium care by enhancing the knowledge, confidence, competence and clinical performance of critical care nurses. Impact: Our findings provide evidence regarding the development and implementation of a simulation‐based education programme in hospitals for health professional education in Taiwan.